Coding structure of highway engineering information model - LIANG Cai; WANG Changhai (Shenzhen Daxue xuebao. Ligong ban)
Model identification code is the key to the data integration and effective transmission of highway engineering information model from the early stage of design to project construction and operation management, so as to form structured data for integrated management and analysis. By studying the existing information model classification and coding system, this paper analyzes the application and existing problems of various information model identification and code breakdown structures such as engineering system breakdown structure coding, space and classification coding, and work breakdown structure coding, comprehensively considers the different needs of construction management, measurement and payment, file management and big data utilization, and puts forward a "five-grade" highway engineering information model with location and version based on ISO 12006-2 framework, covering projects, construction sites, components, classification and coding framework. This model has been applied in the actual engineering construction management information system. The association and data transmission between construction management information and models are effectively realized through the application of model identification coding, which provides a basis for data sharing and exchange between information systems.